Tourism, gastronomy & scientific research : a descriptive analysis of CNPq Research Groups - Gimenes Minasse, Maria Henriqueta Sperandio Garcia (2022)
Scientific research on Tourism and Gastronomy in Brazil has grown in recent decades and has attracted the attention of different researchers, interested in better understanding its development. This article presents the preliminary analyzes of a descriptive study of Research Groups registered with the CNPq in the area of Tourism that have the term Gastronomy among their key descriptors. This article seeks to register their general characteristics, topics researched at the time, methodological approaches, methods and techniques of collection and analysis of the most used data, difficulties in keeping an active and productive Group, research challenges on Tourism and Gastronomy in Brazil, issues that deserve to be better developed in the context of research on Tourism and Gastronomy in Brazil, among other information. Data collection was carried out in two stages. The first consisted of a consultation of the Directory, which allowed obtaining general information about the 26 registered groups; the second was carried out using an electronic questionnaire, consisting of 16 open and closed questions, prepared on the Survey Monkey platform and sent to the leaders of the Groups. 17 completed questionnaires were obtained. Among the main results, the following stand out: the groups are concentrated mainly in the Northeast and Southeast regions; the vast majority of Groups were created in 2010 and favor a cultural perspective. They use, for the most part, mixed approach research, qualitative data collection strategies, and descriptive statistical analysis, content and discourse analysis. The most used methods are case study, ethnography and bibliometric analysis. The main difficulties mentioned to maintain a productive Research Group refer to the composition and dynamics of the team and the lack of funding. The main challenges for conducting research on Tourism and Gastronomy in Brazil were identified as theoretical and methodological difficulties, obtaining resources and difficulty in training new researchers.